Black Writers, White Publishers: A case study of the Bantu Treasury Series in South Africa - Elizabeth LE ROUX (E-REA)
Wits University Press (WUP), South Africa’s oldest university press, is considered a pioneer in the publishing of African-language literature, due to the publication of the long-running Bantu Treasury Series (later to be renamed the African Treasury Series). Along with the mission presses, local-language newspapers and some educational publishers, this publisher played a part in the development of African-language literature in South Africa. But the press would not have earned this reputation without the commitment of Professor Clement Doke. Inspired by the publication of novels in English by black South African authors, Doke established the series to provide a publications outlet in the local African languages. This paper examines the development and impact of the Bantu Treasury Series, with a focus on the authors and their relations with the series editor and publisher.